Durus Al-Lughah Gontory: Interactive Arabic Mobile Learning for Beginners - Dihin Muriyatmoko; Achmad Farouq Abdullah; Zaenury Adhiim Musyafa‟ (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
The goal of the Android mobile application for Arabic learning is to help students who are not alumni of Muslim boarding school in everyday interaction using the Arabic language at Universitas Darussalam Gontor and to function as a medium to introduce Arabic of Pondok Modern Darussalam Gontor version to beginners. The contents come from the book of the first edition of chapter 1 to 12 written by KH. Imam Zarkasyi and KH. Imam Syubani. These books are studied by santri of KMI PMDG of class one. This application applies grammar translation and audiolingual method to learn Arabic for beginners and is developed using ADDIE (analysis, design, development, implementation, and evaluation) approach model. The test was done in six ways: its compatibility with any android device at least 4.5 inchi with the type of android mimimum version of 4.0.4 (Ice Cream Sandwich), an expert material of Arabic language learning give rate score 95%, an expert of media learning give rate score 88.9%, 7 of 11 lecturers of Arabic language give an average score of 81.4%, 6 of 30 students from non-alumni muslim boarding school at this campus give 91.6% and 373 general users via playstore from February 1, 2017, to November 18, 2017, rated 4.9. The result of the overall evaluation of all the tests on this apps shows that this application is relevant to beginner users because of its ease. However, it cannot replace the role of teacher, class, and situation of real Muslim boarding school.